2018
DOI: 10.1111/cfs.12591
|View full text |Cite
|
Sign up to set email alerts
|

What does empathy sound like in social work communication? A mixed‐methods study of empathy in child protection social work practice

Abstract: It is widely accepted that empathy is important for social work practice, yet there are multiple dimensions of empathy and comparatively few studies of empathy as a component of social work skill. To date, published studies have been quantitative, and as a result, we know little about how social workers demonstrate empathy in practice or what skilled empathic practice in child and family social work might sound like. This study contributes to the development of understanding of empathy as a social work skill t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
(41 reference statements)
1
27
0
1
Order By: Relevance
“…As in Lynch et al () work, this study highlighted the behavioural components of the qualities displayed by workers providing support in this context. Not giving up meant persistence, consistency, and patience.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…As in Lynch et al () work, this study highlighted the behavioural components of the qualities displayed by workers providing support in this context. Not giving up meant persistence, consistency, and patience.…”
Section: Discussionsupporting
confidence: 59%
“…The available evidence on supporting individuals facing multiple and complex needs suggests that workers whose professional roles are less defined than those of therapists and typically do no operate within a treatment model need to build successful relationships with their clients by, for example, being available, providing practical help, persisting not enforcing support, and being a “friend” (de Leeuw, van Meijel, Grypdonck, & Kroon, ; Parr, ). Lynch, Newlands, and Forrester () mixed‐method study showed that high levels of empathy were perceived when social workers asked open questions showed curiosity and expressed understanding and interest in the emotions of their clients. Additionally, Parr () highlighted the fact that workers need to challenge clients in a supportive but assertive manner when the quality of the relationship is strong.…”
Section: Background Literaturementioning
confidence: 99%
“… Gibson (2020) found that social work practice in the child protection process often evoked or exacerbated feelings of shame and humiliation in the parents he observed or spoke with. Parents in another study experienced social work interventions as denying them recognition and respect through othering, a deficit-based model of practice, and a failure to understand families’ situation from their perspective ( Gupta et al ., 2018 ) Given that the value base for social work heavily endorses an empathic response to human suffering in arenas such as child protection, it is surprising to find that empathy in practice appears to exist at relatively low levels ( Lynch et al , 2019 ).…”
Section: Social Work Legitimacymentioning
confidence: 99%
“…Various authors have drawn attention to the erosion and even collapse of the so-called welfare states due to changes in public social policies [9][10][11]. The problems generated by these measures cause welfare states to face high rates of poverty and inequality [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, in recent years, research has shown that social services professionals, particularly social workers, are also suffering the consequences of the erosion of social services [32,33]. Public social policy reform has led to cutbacks in human and material resources, in turn creating a huge workload for social workers [12].…”
Section: Introductionmentioning
confidence: 99%